TES KESEGARAN JASMANI MAHASISWA PUTRI PROGRAM STUDI PGMI SEMESTER II STAINU TEMANGGUNG - Al Hakim, Muhammad Fadloli (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims to determine the level of physical fitness of female college student in the second semester of PGMI STAINU Temanggung, amounting to 25 people. The method of this research is to use quantitative descriptive methods. While the data collection technique uses tests, the instrument used in this study is in the form of the Indonesian Physical Freshness Test (TKJI). Data analysis techniques using the percentage formula. The results showed that of 25 PGMI students in the second semester of the 50 meter running test with a score of 3 (moderate), a bent elbow hanging test with a value of 2 (less), a reclining sitting test value of 3 (moderate), a vertical jump test with a value of 3 (moderate), and finally the 600 meter test run with a score of 3 (moderate). The conclusion is that PGMI female college student in the second semester of STAINU Temanggung have a physical fitness level with a total of 14 in the medium category.